Perfil de presión uretral - Valdevenito S., Juan Pablo (Revista Hospital Clínico Universidad de Chile, 2018)
The “urethral pressure profile” is a graph indicating the intraluminal pressure along the length of the urethra and the “urethral closure pressure profile” is given by the substraction of intravesical pressure (pves) from urethral pressure (pura). Both aim to represent the ability of the urethra to prevent involuntary leakage of urine on efforts or exertion. The continuous measurement of pves also allows the detection of detrusor contractions. In this article we will refer to its terminology, the necessary equipment to carry it out, the examination technique, its morphology in women and men, and the stress urethral pressure profile in women. The most important parameter is the “maximum urethral closure pressure”, which is the maximum difference between pura and pves; a value ≤ 20 cm H2O participates in the urodynamic definition of intrinsic sphincter deficiency (together with an abdominal leak point pressure ≤ 60 cm H2O). However, it must be taken into account that the different techniques used for its measurement has led to inconsistent results, which makes their acceptance in clinical practice difficult.